Development of Android Based Laboratory Asset Monitoring and Inventory Application - Parenreng, Mardawia Mabe; Nur, Fajria; Asriyadi, Asriyadi (Politeknik Negeri Ujung Pandang, 2020)
Each laboratory has a person in charge (technician) that has a duty of serving the laboratory in term of operational and maintenance. The main task of a technician is to record and monitor the condition and completeness of laboratory equipment in the laboratory. The data collection process is done by writing a tool request form, therefore mistakes often occur. In this research, an Android-based laboratory asset monitoring and inventory application was made. By using the application, it is expected that technicians become easier to make any duties of reports including report of damaged laboratory equipments, request for reparation, the unavailable practical materials etc simply by using a Smartphone. Testing the application with the Black-Box testing method to investigate the function of each application component whether it is running well or not. The results obtained from the Black-Box test are the functions of each component were running as expected. The case study is conducted for Electrical Engineering Department at State Polytechnic of Ujung Pandang (SPUP)